The Concept And Role Of The Student Centered Learning Model In Adolescent Akhlaq Education - Cecep Sobar Rochmat; Rosendah Dwi Maulaya; Annisa Avilya (At-Ta'dib, 2022)
One of the extrinsic causes of moral decadence in adolescents is the failure of teachers to teach akidah Akhlaq material. Where the lessons of Akidah Akhlaq fail to be lived and practiced in daily life by students. The learning model is a contributing factor to successes and failures in teaching. This paper aims to describe the role of the Student Centered Learning learning model in adolescent moral education towards the material of Akhlak akidah in madrasahs. The research carried out is qualitative research with literature studies.  The researchers found that SCL patterns in Akidah Akhlaq learning influenced teachers' success in teaching. The application of SCL for learners provides hands-on experience in learning. Akidah Akhlaq's learning becomes more meaningful. If you have found concrete meaning in learning, it will facilitate the steps towards the process of passion and practice in life. Through the characteristics of active, constructive, collaborative, enthusiastic, dialogical, contextual, reflective, multisensory, and high-order learning skills training provides satisfactory learning outcomes. The education of akhlaq teenagers in this age is something very important considering how difficult the morals of today's teenagers are. The SCL method can be applied to support the success of moral education in adolescents.